2016
DOI: 10.1016/j.prevetmed.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple imputation in veterinary epidemiological studies: a case study and simulation

Abstract: The problem of missing data occurs frequently in veterinary epidemiological studies. Most studies use a complete case (CC) analysis which excludes all observations for which any relevant variable have missing values. Alternative approaches (most notably multiple imputation (MI)) which avoid the exclusion of observations with missing values are now widely available but have been used very little in veterinary epidemiology.This paper uses a case study based on research into dairy producers' attitudes toward mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Multiple imputation 25 followed by generalised estimating equations (MI‐GEE analysis) 26 was used for analysis. Data were stored and processed in Access and Excel.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple imputation 25 followed by generalised estimating equations (MI‐GEE analysis) 26 was used for analysis. Data were stored and processed in Access and Excel.…”
Section: Methodsmentioning
confidence: 99%
“…No covariate was missing at a rate that exceeded 15%. Simulation studies have suggested that multiple imputation provides equivalent or better coverage and bias than complete case analysis, even when missingness is not at random 12 13. We therefore used multiple imputation rather than a complete case analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, instead of calling the veterinarian when discovering a sick cow, this data set showed a negative association between the average longevity of the herd and farmers that most likely “Initiated treatment on one’s own” when discovering an unhealthy cow. As multiple imputation analyses generally produce less biased results than complete case analyses [ 24 ], more weight is put on the results from the multiple imputation model. It is generally recommended to use a large number of predictors in the imputation process, and in this case we used all available data from the questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple imputation is a flexible, simulation-based statistical technique for handling missing data [ 23 , 24 ]. It has been shown that multiple imputation analyses generally produce less biased results than complete case analyses [ 24 ]. Multiple imputation of missing predictor values was carried out using the outcome variable and all predictors for which data were missing.…”
Section: Methodsmentioning
confidence: 99%